Between projected shadows, mobile screens and shadow performers: new horizons for stage imagery (A Luz em Cena: Revista de Pedagogias e Poéticas Cenográficas, 2024)
The text presents a reflection on the use of screens and other mobile projection supports for the creation of 'lumino-kinetic' devices capable of generating transformations in the scenic space and attributing new meanings to visual dramaturgy. The central ideas revolve around the relationship between the performance of the contemporary shadow performer and these devices, which include objects, scenography, light and shadow, space, and the creation of a poetic and symbolic universe through animation.